Price, Service and Consumer Satisfaction: A Comparative Study of Traditional and Modern Markets - Tiana Setianingrum; Fatikah, Nur; Miftakul Huda; Fianto Ady S; Krisdayanti; Daniel Rikzen S; Rudolf Flotora A; Restu Fauzi; Raflika Yogi; M. Resa F (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This study aims to compare the level of consumer satisfaction when shopping in modern markets and traditional markets in the city of Cikarang. This study uses a quantitative descriptive method involving 111 respondents who live in Cikarang. The sampling technique used is probability sampling. The results of the study indicate that consumers who shop in modern markets with adequate facility dimensions have a higher level of satisfaction. Conversely, consumers who shop in traditional markets are satisfied with the affordable price dimension. In conclusion, modern markets are considered satisfying by consumers, but prices in traditional markets remain the main point of interest